Changes in Climate, Forest Phenology, and Forest Disturbances Around Western Lake Superior - Garcia, Matthew (Proceedings of the Wisconsin Space Conference, 2017)
This work proceeds from two hypotheses. First, we can explain much of the observed seasonal and year-to-year variability in forest phenology using weather and climate observations. Seasonal forest phenology is driven by the progress of the warm season: it is observed that frost events can stop spring growth and that seasonal droughts can degrade forest health. What we don’t quite know yet is how strong the roles of climate change and weather variability are in these processes. Second, linking anomalies in observed phenology (by remote sensing methods) with climatological analyses can indicate the occurrence, extent, and possible causes of forest disturbances. We pursue two primary interests here: (1) observations of regional climatology and its variability in the area around western Lake Superior, and (2) identifying the influence of climate variability on forest phenology and disturbances in that area.